How to love - Thich, Nhat Hanh (Parallax Press, 2015)
How to Love explores the true meaning of love through mindfulness. Thich Nhat Hanh teaches that love begins with understanding, compassion, and deep presence. The book offers simple yet powerful insights on how to love yourself and others genuinely, without attachment or expectations. It emphasizes listening, speaking with kindness, and being fully present as the foundation of meaningful relationships.